Fría venganza : el primer caso del sheriff Walt Longmire - Johnson, Craig, 1961-; Porras Sánchez, María; Johnson, Craig, 1961- (Madrid : Ediciones Siruela, 2012)
After decades of peace between the white and Native American communities of early American Wyoming, a young man who was once convicted for raping a Cheyenne girl is found dead, prompting sheriff Walt Longmire, his deputy Victoria Moretti, and friend Henry Standing Bear to investigate.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Longmire, Walt -- Fiction; Absaroka Range (Mont. and Wyo.) -- Fiction; Sheriffs -- Fiction; Wyoming -- Fiction; Detective and mystery fiction; Electronic books